Building the Rainbow Nation. A critical analysis of the role of architecture in materializing a post-apartheid South African identity - Raedt, Kim (Afrika Focus, 2012)
Soon after apartheid was abolished in 1994, the quest for a new, ‘authentic’ South African identity resulted in the emergence of the "Rainbow Nation" idea, picturing an equal, multicultural and reconciled society. As architecture is considered a crucial element in the promotion of this Rainbow identity, the country witnessed a remarkable "building boom" with its apogee roughly between 1998 and 2010. Huge investments have been made in state-driven projects which place the apartheid memory at the center of the architectural debate – mostly museums and memorials. However, the focus of this paper shall lie on another, less highlighted tendency in current architectural practice. This paper demonstrates that, through the construction of urban community services, South African architects attempt to materialize the Rainbow Nation in a way that might be closer to the everyday reality of society. Key words: architecture, post apartheid, Cape Town, South Africa, identity